Factors Defining Human Adipose Stem/Stromal Cell Immunomodulation in Vitro - Marwa Mahmoud; Mazen Abdel-Rasheed; Eman Reda Galal; Rehab R. El-Awady (Stem Cell Reviews and Reports, 2024)
Human adipose tissue-derived stem/stromal cells (hASCs) are adult multipotent mesenchymal stem/stromal cells with immunomodulatory capacities. Here, we present up-to-date knowledge on the impact of different experimental and donor-related factors on hASC immunoregulatory functions in vitro. The experimental determinants include the immunological status of hASCs relative to target immune cells, contact vs. contactless interaction, and oxygen tension. Factors such as the ratio of hASCs to immune cells, the cellular context, the immune cell activation status, and coculture duration are also discussed. Conditioning of hASCs with different approaches before interaction with immune cells, hASC culture in xenogenic or xenofree culture medium, hASC culture in two-dimension vs. three-dimension with biomaterials, and the hASC passage number are among the experimental parameters that greatly may impact the hASC immunosuppressive potential in vitro, thus, they are also considered. Moreover, the influence of donor-related characteristics such as age, sex, and health status on hASC immunomodulation in vitro is reviewed. By analysis of the literature studies, most of the indicated determinants have been investigated in broad non-standardized ranges, so the results are not univocal. Clear conclusions cannot be drawn for the fine-tuned scenarios of many important factors to set a standard hASC immunopotency assay. Such variability needs to be carefully considered in further standardized research. Importantly, field experts’ opinions may help to make it clearer. Graphical Abstract Parameters that promote ASC immunosuppression on immune cells. Activation of immune cells induces their proliferation and differentiation and presence of ASCs modulates/suppresses such consequences. Augmented immunosuppressive effects of ASCs can be introduced in direct contact with the immune cells and via complementing the repeatedly reported experimental settings (texts in grey shapes). Abbreviations: ASCs: adipose tissue-derived stem/stromal cells, IFN-ɤ: Interferon gamma, MLR: Mixed lymphocyte reaction, TNF: Tumor necrosis factor.

Zinc Oxide Nanoparticles Promise Anticancer and Antibacterial Activity in Ovarian Cancer - Ahmed Bakr Mousa; Raghda Moawad; Yasmine Abdallah; Mazen Abdel-Rasheed; Azza M. Abdel Zaher (Pharmaceutical Research, 2023)
Background Ovarian cancer is the most lethal cancer in gynaecology. Surgery, chemotherapy, and radiotherapy are the most often used cancer-fighting strategies. Post-surgery infection is fairly prevalent, especially among people with insufficient immunity. Zinc oxide nanoparticles (ZnOnps) have amazing biomedical features as anticancer and antibacterial agents. Methods We investigated the behaviour of ZnOnps synthesized by green methods on ovarian cancers using established human ovarian cancer cell lines, besides the antibacterial action toward models of gram + ve and gram -ve bacteria. The cytotoxic effect of ZnOnps was calculated using a Sulforhodamine B (SRB) trial. Staphylococcus aureus (S. aureus) and Escherichia coli ( E. coli) were tested as models for gram + ve and gram -ve bacteria. The selected bacteria were subjected to concentrations of 20, 40, 80, and 100 μg/ml. Results The synthesized ZnOnps induced 50% inhibitory concentration (IC50) at a concentration of 27.45 μg/ml. The diameter of inhibition ranged between 20.16 ± 0.16 and 27 ± 0.57 mm for S. aureus and 25.66 ± 0.33 to 31 ± 0.33 mm for E. coli . ZnOnps antagonistic effect statistically differed with neomycin, cefaclor, and cefadroxil. Conclusions Green synthesis of ZnOnps is easily prepared, low cost, non-toxic, and eco-friendly. Their cytotoxic action on SKOV3 cells and their antibacterial characteristics pave the way to be an alternative therapy for ovarian cancer and S. aureus and E. coli infection.

Influence of type 2 diabetes and obesity on adipose mesenchymal stem/stromal cell immunoregulation - Marwa Mahmoud; Mazen Abdel-Rasheed (Cell and Tissue Research, 2023)
Type 2 diabetes (T2D), associated with obesity, represents a state of metabolic inflammation and oxidative stress leading to insulin resistance and progressive insulin deficiency. Adipose-derived stem cells (ASCs) are adult mesenchymal stem/stromal cells identified within the stromal vascular fraction of adipose tissue. These cells can regulate the immune system and possess anti-inflammatory properties. ASCs are a potential therapeutic modality for inflammatory diseases including T2D. Patient-derived (autologous) rather than allogeneic ASCs may be a relatively safer approach in clinical perspectives, to avoid occasional anti-donor immune responses. However, patient characteristics such as body mass index (BMI), inflammatory status, and disease duration and severity may limit the therapeutic utility of ASCs. The current review presents human ASC (hASC) immunoregulatory mechanisms with special emphasis on those related to T lymphocytes, hASC implications in T2D treatment, and the impact of T2D and obesity on hASC immunoregulatory potential. hASCs can modulate the proliferation, activation, and functions of diverse innate and adaptive immune cells via direct cell-to-cell contact and secretion of paracrine mediators and extracellular vesicles. Preclinical studies recommend the therapeutic potential of hASCs to improve inflammation and metabolic indices in a high-fat diet (HFD)-induced T2D disease model. Discordant data have been reported to unravel intact or detrimentally affected immunomodulatory functions of ASCs, isolated from patients with obesity and/or T2D patients, in vitro and in vivo. Numerous preconditioning strategies have been introduced to potentiate hASC immunomodulation; they are also discussed here as possible options to potentiate the immunoregulatory functions of hASCs isolated from patients with obesity and T2D.